The Importance of Studying Indonesian Language - Anita Candra Dewi; Ibrah Muchtiz M. Dien; Jelita Saman; Chintya April Liyon Daniel; Abjan Sulaiman Garurah; Julianto Buttu Karaeng (MultiTech Publisher, 2023)
This article was written to provide information about the importance of learning Indonesian in higher education. Indonesian is a national language that must be preserved and its rules must be observed. The use of Indonesian still experiences many inaccuracies because we are not aware of the importance of paying attention to rules, spelling and accuracy in writing and pronunciation of Indonesian. The correct use of Indonesian is intensively introduced from elementary school to university. By introducing the use of good language, it is hoped that it will foster a sense of love for the Indonesian nation and become a shared responsibility to apply it in everyday life, one of which is in academic and educational environments.